The care of patients with Mayer-Rokitansky-Küster-Hauser syndrome (MRKH) - Grażyna Stadnicka; Celina Łepecka-KLusek; Anna Bogusława Pilewska-Kozak; Agnieszka Pawłowska-Muc; Agnieszka Bałanda-Bałdyga (Kazimierz Wielki University, 2017)
The MRKH syndrome has a negative impact on the psychosocial status of a patient and her family. The treatment of aplasia/hypoplasia of the vagina requires an interdisciplinary approach. The choice of treatment and its acceptance by a patient is crucial for the successful therapy. Therefore, it requires careful selection of treatments suited for anatomical conditions and patient's emotional state and also good cooperation between a patient and the therapeutic team at every stage of treatment. Young women should be mentally and substantively prepared for phantomisation of vagina and undertaking sexual activity. To ensure a proper functionality of the newly formed vagina, the sexual care is indispensable for many women with the MKHR syndrome and their partners.